Entornos virtuales de enseñanza-aprendizaje en el proceso académico en los estudiantes de octavo año paralelo “A”, de la unidad educativa “Guaranda” de la cuidad de Guaranda provincia Bolívar durante el año 2022 - Arguello Lara, Bryan Armando (2022)
In the present research work, the topic "Virtual teaching-learning environments in the academic process in the eighth year parallel students "a", of the "Guaranda" educational unit of the city of Guaranda province Bolívar during the year 2022”, where it seeks to establish knowledge about the use and management of virtual platforms. The objective was to strengthen the learning of natural sciences, through the virtual teaching-learning environment, to improve the academic process in students of eighth year parallel "A" of said institution. For which a virtual environment was implemented following the guidelines of the PACIE methodology. The research applied in this work is of a bibliographic type because necessary information is obtained from the variables proposed for the search of documents; it is historically logical because the antecedents referring to the proposed investigation were analyzed; it is deductive because it is used to apply this virtual learning environment and inductive because it allows knowing the results of the implemented application. The theoretical framework was elaborated, with bibliographical research in books, magazines, brochures and the Internet that served as an aid to obtain necessary and pertinent information, constituting a true bibliographical support. It was recommended to implement a virtual teaching-learning environment in the teaching of Natural Sciences with the use of the MOODLE educational platform, for which a manual will be delivered for its management and use by teachers and students.